2012
DOI: 10.1161/hypertensionaha.111.180844
|View full text |Cite
|
Sign up to set email alerts
|

Increased Angiotensin II–Induced Hypertension and Inflammatory Cytokines in Mice Lacking Angiotensin-Converting Enzyme N Domain Activity

Abstract: Angiotensin converting enzyme (ACE) is composed of the N- and C-terminal catalytic domains. To study the role of the ACE domains in the inflammatory response, N-KO and C-KO mice, models lacking one of the two ACE domains, were analyzed during angiotensin II-induced hypertension. At 2 weeks, N-KO mice have systolic blood pressures that averaged 173 ± 4.6 mm Hg, which is more than 25 mm Hg higher than the blood pressures observed in wild-type or C-KO mice (146 ± 3.2 and 147 ± 4.2 mm Hg). After 3 weeks, blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(36 reference statements)
0
10
1
1
Order By: Relevance
“…In this study, chronic Ang II infusion was performed at 1000 and 2000 ng/kg per min to examine the effects of distal tubule–dominant overexpression of ATRAP on the Ang II–mediated BP increase. Although the higher dose of Ang II (2000 ng/kg per min) is reported to provoke a reduction in food intake and to cause Ang II–induced wasting and skeletal muscle atrophy, 17 the lower dose of Ang II (1000 ng//kg per min) has been used in many previously performed experiments in mice, 18,19 and suppression of the Ang II–induced BP increase by the distal tubule–dominant overexpression of ATRAP was observed with both the lower and higher doses of Ang II in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, chronic Ang II infusion was performed at 1000 and 2000 ng/kg per min to examine the effects of distal tubule–dominant overexpression of ATRAP on the Ang II–mediated BP increase. Although the higher dose of Ang II (2000 ng/kg per min) is reported to provoke a reduction in food intake and to cause Ang II–induced wasting and skeletal muscle atrophy, 17 the lower dose of Ang II (1000 ng//kg per min) has been used in many previously performed experiments in mice, 18,19 and suppression of the Ang II–induced BP increase by the distal tubule–dominant overexpression of ATRAP was observed with both the lower and higher doses of Ang II in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These data come from an analysis of the NKO mice discussed above [82, 85]. Figure 2 shows data from an experiment in which thioglycollate-elicited peritoneal macrophages were collected and exposed in vitro to lipopolysaccharide (LPS) for 18 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Further, increased TNFα production was found in peritoneal macrophages from N-KO mice made hypertensive by angiotensin II infusion. In vitro, N-KO macrophages over produce the pro-inflammatory cytokine IL-12 in response to LPS but produce less of the anti-inflammatory cytokine IL-10 [85]. While these findings clearly show an effect of the ACE N-domain on cytokine production, what is not clear is whether this is a direct effect on the biochemistry of cytokine production, or whether the biochemical milieu within the ACE N-KO mice somehow instructs macrophages along a developmental program leading to changes in differentiation state and an intrinsically higher inflammatory response to pro-inflammatory stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…A study of angiotensin II-induced hypertension in the NH 2 -terminus inactivated mice (called N-KO) showed augmented hypertension compared with WT (107). Interestingly, ex vivo studies showed that macrophages from the N-KO had augmented pro-inflammatory cytokine profile, suggesting that accumulated Ac-SDKP may impact macrophage polarization toward the M1 phenotype (107). By contrast, several other models of inflammation, including experimental autoimmune myocarditis, found reduced pro-inflammatory cytokine markers in the presence of Ac-SDKP (100).…”
Section: Role Of Ace Outside the Rasmentioning
confidence: 99%
“…Whether this tetrapeptide confounds the generally beneficial impact of ACE on tumor immunology remains an interesting area of investigation. The availability of the N-KO mouse model (50,107) should not only provide answers to these important questions but also enable evaluation of the role Ac-SDKP on immune cells without the potential complicated effects of other ACE susbtrates and peptides that accumulate in the setting of routine ACE inhibitors, which block both termini of the ACE protein.…”
Section: Role Of Ace Outside the Rasmentioning
confidence: 99%